Research on the spatial effect of foundation pit under asymmetric loads - Xu, Changjie; Lin, Zhaorui; Jiang, Yalong; Shi, Yufeng; Fan, Xiaozhen; Xiong, Zheng; Liu, Yangfeng (Frontiers in Materials, 2022)
Current foundation pit designs give little consideration to the development of spatial effects under load. This research describes the evolution of the spatial effects of foundation pits considering internal support and external loads is described. Based on the existing concept of "plane strain ratio", the term "plane strain ratio considering maximum surface settlement" is proposed to characterize the spatial effects of an asymmetric foundation pit. On this basis, a series of finite element model calculations were carried out using Nanchang Aixi Lake foundation pit, including (1) the calculation of simulated actual conditions, (2) the calculation of simulated full symmetric load, and (3) the calculation of simulated asymmetric load. The results indicate that for the symmetric condition at 20 kPa and below, the spatial effect range increases as the load increases. For the symmetric condition above 20 kPa, the load has a negligible impact on the spatial effect range. Under the asymmetric loading condition, the difference between the spatial effect on the side with larger load and that on the side with smaller load is significant. On the side with larger load, the spatial effect of the condition below 30kPa is reduced than that of the corresponding symmetrical load. On the side with smaller load, the spatial effect of the working condition above 80kPa increases compared with that of the corresponding symmetrical load. Given are the modified fitting equations that take into account the influence range of spatial effect on both sides of the foundation pit under symmetrical and asymmetrical loads. The verification computation confirmed the applicability of the fitting formula.